A novel and improved UHPLC-QTOF/MS method for the rapid analysis of the chemical constituents of Danhong injection. Issue 14 (18th March 2016) - Tang, Jin-fa; Li, Wei-xia; Tan, Xiao-jie; Li, Peng; Xiao, Xiao-he; Wang, Jia-bo; Zhu, Ming-jun; Li, Xue-lin; Meng, Fei
Abstract : Danhong injection (DHI), one of the best-selling traditional Chinese medicine injections (TCMIs), is used extensively for treating myocardial infarction, atherosclerosis, coronary heart disease, and traumatic intracranial hematoma in clinics. Abstract : Danhong injection (DHI), one of the best-selling traditional Chinese medicine injections (TCMIs), is used extensively for treating myocardial infarction, atherosclerosis, coronary heart disease, and traumatic intracranial hematoma in clinics. It has attracted increasing attention as one of the most popular and valuable herbal medicines. However, the systematic analysis of the chemical constituents of DHI is difficult and thus has not been well established. In this paper, rapid, sensitive, and reliable ultra high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-QTOF/MS) was established to characterize the components of DHI. And the UNIFI software with the Traditional Medicine Library was applied to identify the chemical constituents of DHI for the first time, which is simpler and more effective. Under the optimized conditions, a total of 44 peaks including nucleotides, phenolic acids, and flavonoid glycosides were identified or tentatively characterized by comparing the retention time and MS data. The results may provide useful information for the further study of the pharmacology and mechanism of DHI. Furthermore, with the introduction of the UNIFI software into the analysis of TCM, this will provide a type of validated rapid and high-throughput methodology for the identification of constituents in Chinese herbal prescriptions; we expect that this approach would be useful for the screening and characterization of compounds in other famous TCM products.